Bimetallic Ni-Pd synergism-mixed metal catalysis of the mizoroki-heck reaction and the suzuki-miyaura coupling of aryl bromides - Kashid, Abhijit A.; Patil, Dharmaraj J.; Mali, Ramling D.; Patil, Vijay P.; Neethu, T. V.; Meroliya, Heena K.; Waghmode, Shobha A.; Iyer, Suresh (Catalysis Letters, 2021)
A combination of Pd and Ni complexes activated aryl bromides for the thermal Mizoroki-Heck reaction and Suzuki coupling giving high yields in short reaction times. A thermal redox mechanism probably occurs whereby Ni complex transfers electron and reduces the Pd (II) to Pd (0) which then takes the reactants through the standard protocol of oxidative-addition, migratory insertion and reductive elimination, typical for the Mizoroki-Heck reaction and the Suzuki coupling. [GRAPHICS] .
Keywords: Bimetallic catalysis; Mizoroki-Heck; Nickel complexes; Pd(OAc)2; Suzuki coupling